1998
DOI: 10.1539/joh.40.270
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Silicon Compounds in Semiconductor Industries

Abstract: Abstract:Toxicity of Silicon Compounds in Semiconductor Industries: Hiroshi NAKASHIMA, et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 7 publications
0
23
0
1
Order By: Relevance
“…However, the use of these commercial precursors as a source of silica is impractical since the price of these chemicals is expensive and it is harmful to health and environment [6,7]. Thus, finding a new source of silica that is cheaper, safer, and environmentally friendly is crucial [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of these commercial precursors as a source of silica is impractical since the price of these chemicals is expensive and it is harmful to health and environment [6,7]. Thus, finding a new source of silica that is cheaper, safer, and environmentally friendly is crucial [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…Nakashima et al reported that acute exposure can cause death TEOS. (Nakashima et al, 1998) Thus, there is a need to find a silica precursor safer, cheaper, and more environmentally friendly. .…”
Section: Introductionmentioning
confidence: 99%
“…In this method, silicone oil has been used as starting materials used to deposit SiO 2 films. It is a promising materials because of their low cost, high thermal stability and high safety [29,30], compared with tetra-ethyl-ortho-silicate [TEOS:Si(OC 2 H 5 ) 4 ] [31,32], a widely used as a common source materials to deposit SiO 2 films. TEOS is also toxic to human eyes and throats.…”
Section: Introductionmentioning
confidence: 99%